Poland and the Knowledge Economy : Enhancing Poland's Competitiveness in the European Union - Goldberg, Itzhak (Pruszkow, Poland: Rewasz Publishing House and the World Bank, 2013)
The Poland Knowledge Economy Assessment (KEA) aims to provide policy options for securing sustainable growth, and improving competitiveness, by creating an environment conducive to business development, and investment in general, as well as to knowledge generation and absorption via innovation, and learning, in particular, as well as by stimulating investment in innovation, and in learning systems. This KEA argues that efficient, and relevant lifelong learning systems, Information and Communication Technologies (ICT), institutions and funding mechanisms to support innovative research and development (R&D), are essential components of the National Innovation System (NIS). The foremost theme of this report is securing sustainable growth and competitiveness in Poland, by stimulating investment in R&D, and in appropriate learning systems, which have a key role in developing a country's absorptive capacity-the ability to identify, assimilate, and exploit knowledge from both domestic, and external sources. Therefore, policies that support the development of inter-firm linkages, and the capacity to absorb new knowledge that can be gained through such linkages, are crucial elements. As regards R&D and innovation, efforts need to be made to build institutions and provide financial incentives aiming to increase Polish R&D. Nevertheless, it should be stressed that an improvement in the business environment in Poland is a necessary condition for raising the R&D within firms. Most importantly, efforts need to be made to increase the quality, and relevance of the formal education system, ensure the provision of life long learning systems to the entire population, and improve the linkages between academia, the scientific, and business communities that assist the transfer of technology in other countries. It is proposed that the regulatory framework be updated to the European Union (EU) 2002 level, and that the capacity, and market credibility of the Office of Telecommunications and Post Regulation (the regulatory authority), be strengthened in order to sustain competition. The implementation of e-government services for businesses, as well as citizens is key for improving the efficiency, and competitiveness of Polish business.